Lean Consumption Implementation for Acceleration Improvement in Executive Outpatient Wait Time over Hermina Hospital Bekasi - Barlian Susanti; Tantri Yanuar Rahmat Syah; Ketut Sunaryanto (Penerbit Kemala Indonesia, 2020)
The implementation of “lean hospital” has been conducted in several countries. The most implementation resulted in the service acceleration and cost efficiency there are still few hospitals in Indonesia that implement “lean consumption” in their services. Thus, this study aimed to test the lean consumption at the hospital with “Lean Consumption Map” (LCM) method and using “Define, Measure, Analyze, Improve, and Control” (DMAIC) instrument. This empirical study is expected to give insight to the management in the hospital to make acceleration improvement of the outpatient service wait time by comparing the wait time length before and after the test with LCM method was conducted. The analysis in this study used Time Plot Series, Value Added Assessment, FMEA and LCM, with an inductive qualitative method. The final result shows that the lean consumption implementation is applicable through the DMAIC instrument and LCM method in the acceleration improvement of the executive outpatient wait time in Hermina Hospital Bekasi. Furthermore, the result shows the illustration of the time acceleration of the outpatient wait time on the customer’s side is improved from 95 minutes to 65 minutes; whereas, on the provider’s side, the time acceleration is improved from 137 minutes to 90 minutes.